Interpretasi Data Mikrotremor Melalui Analisis Horizontal To Vertical Spectral Ratio (HVSR) untuk Mikrozonasi Bahaya Gempa Seismik di Kota Baubau - Rudin; Jamhir Safani (Jurnal Rekayasa Geofisika Indonesia, 2024)
Research has been carried out on seismic hazard microzonation in the city of Bau – bau using microtremor data. The aim of this research is to determine the seismic vulnerability index based on horizontal to vertical spectral ratio (HVSR) analysis and create a dominant frequency microzonation map (F0), dominant period map (T0), amplification factor map (A0), and seismic vulnerability index map (Kg) from microtremor data which can describe the level of vulnerability of an area to seismic hazards. Microtremor measurements were carried out using a portable three-component seismograph (TDS. 303), the data was analyzed with gepsy software via the HVSR method. The research results show that the distribution of dominant frequency values ​​(F0), ranges from 0.4795 Hz to 16.6383 Hz, dominant period values ​​(T0), ranges from 0.0601 seconds to 2.0854 seconds, amplification factor values ​​(A0), ranges from 1.2285 to 4.9043, and the seismic vulnerability index (Kg) value ranges from 0.1043 to 11.0276. The values ​​(F0), (T0), (A0), and (Kg) are interpreted by referring to literature data and surface geological maps of the research area. The results show that the study area has a small portion of sediment layers that are vulnerable to seismic hazards.